Pembangunan Infrastruktur Dalam Mereduksi Tingkat Kemiskinan Di Indonesia Bagian Barat - Martia Wirlis, Wiwit; Aimon, Hasdi (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research aims to determine the influence of the development of road infrastructure, sanitation infrastructure and telecommunications infrastructure in reducing poverty levels in Western Indonesia. The method used is panel data regression analysis consisting of time series data for the period 2014 to 2022 and a cross section of 20 provinces in the Western Region of Indonesia. By using E-views 12 with the random effect model analysis method, the results were found that 1) road infrastructure has been able to reduce poverty levels in the Western Region of Indonesia, but has not had a significant influence. 2) sanitation infrastructure has been able to reduce poverty levels in the Western Region of Indonesia but has not had a significant impact. 3) telecommunications infrastructure has been able to reduce poverty levels in the Western Region of Indonesia and has had a significant influence. 4) the variables of road infrastructure, sanitation infrastructure and telecommunications infrastructure simultaneously have a significant influence on poverty levels in the Western Region of Indonesia. Infrastructure development has an important role in alleviating poverty, so it requires the provision of adequate infrastructure.